2016
DOI: 10.4283/jmag.2016.21.1.141
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rotating Magnetic Field on Enterotoxin Genes Expression in Staphylococcus Aureus Strains

Abstract: Staphylococcus aureus cultures exposed to rotating magnetic field (RMF) were studied in order to analyse the possible induced changes in staphylococcal enterotoxin genes (se) expression. Liquid cultures of S. aureus strains carrying different se were exposed to the RMF of magnetic frequency 50 Hz and magnetic induction 34 mT for 10 h at 37 °C. Three time points of bacterial growth cycle were considered for RNA extractions. Gene expression analyses were evaluated using real-time quantitative PCR method. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The results of basic microbiological studies presented in this article were an extension of the previous studies in this area presented in the cited reference works [ 34 , 35 , 37 , 38 , 39 , 40 ]. The cited experimental studies were focused on the influence of the interaction between RMF and antibiotics, as well as the analysis of bacterial colony growth dynamics, the metabolic activity of cells, as well as genetic activity of selected bacterial species exposed to RMF.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The results of basic microbiological studies presented in this article were an extension of the previous studies in this area presented in the cited reference works [ 34 , 35 , 37 , 38 , 39 , 40 ]. The cited experimental studies were focused on the influence of the interaction between RMF and antibiotics, as well as the analysis of bacterial colony growth dynamics, the metabolic activity of cells, as well as genetic activity of selected bacterial species exposed to RMF.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, Giorgi et al [ 49 ] observed that mini-Tn10 and Tn5 transposition decreased under sinusoidal MF and increased under pulsed-square MF. Finally, Fijałkowski et al [ 35 ] reported a lower expression level of sea , seb , sec , sed , and see genes under RMF influence compared to non-exposure samples. Interestingly, these authors observed lower expressions of the sea gene compared to our data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also shown that the treatment affected the growth rate of the microbe. 29,30 Our point of view regarding the variation in gene expression of the genes under study is mainly due to strain variation, as different strains of S. aureus might react differently to the treatments under study and thus led to the variations. On the other hand, the effect of each treatment on the up or down regulation of the target genes is unclear, as no study has explored such type of treatments on those genes.…”
Section: Gene Expression Of Meca Genementioning
confidence: 99%